Qandeel e adab Qwaid o insha for class 6 - Saeeda Maqsood (Lahore: Asian Educational Publisher., 2014)
Qandeel-e-Adab Qawaid-o-Insha: Book 6 is designed to further enhance students' understanding of Urdu grammar and writing skills. The book offers a comprehensive introduction to key grammatical concepts, including sentence structure, tenses, and punctuation, while also guiding students in creative and formal writing. Through a range of exercises, the book helps students apply grammar rules in practical contexts and improve their expression in both written and spoken Urdu. Focused on building a solid foundation in language skills, this textbook is an essential resource for Class 6 students looking to strengthen their command of Urdu grammar and composition.